Phytochemical And Selected Pharmacological Studies Of Standardized Fruit Extracts Of Morinda Citrifolia Linn - Beh , Hooi Kheng (2012)
Morinda citrifolia is commonly used in Malaysia by locals as traditional medicine for various diseases. Currently there are eleven registered commercial products of Morinda citrifolia fruit available in Malaysia. In this study, preliminary phytochemical screening and physico-chemical studies of the fruit powder were attempted and quality parameter involving chromatographic profiling of the extracts were carried out for standardization.